Epidemiological aspects of exogenous poisoning in children under the age of nine in the State of Maranhão in the period from 2010 to 2017 (Research, Society and Development, 2020)
Exogenous intoxications make up a group of harmful effects that are reflected in clinical and laboratory manifestations. Exogenous intoxications in childhood represent an important public health problem worldwide. As it is a very recurrent case among the population, it is necessary to bring exogenous intoxications in children to the center of discussions. Thus, the objective of this work was to verify the epidemiology of the main exogenous intoxications in children under nine years old in the State of Maranhão in the years 2010-2017. This is a descriptive, retrospective study with a quantitative approach to data extracted from the Information System for Notifiable Diseases (SINAN) of the Informatics Department of the Unified Health System (DATASUS), related to cases of exogenous poisoning of children in the age group between 0 to 9 years old from the State of Maranhão in the period 2010-2017. The results show that in the state of Maranhão, a total of 1419 cases were reported in the years analyzed, the number of confirmed cases of intoxication in children has increased over the years, the biggest cause of intoxications is the class of drugs, regarding the zone, greater prevalence in the urban area is notable and the majority of cases of poisoning were accidental. Thus, it can be concluded that the data obtained fostered the need for health services, for the prophylactic prevention of these occurrences, as well as the implementation of socio-educational measures in order to mitigate intoxications in children.